2018
DOI: 10.1038/s41598-018-33566-w
|View full text |Cite
|
Sign up to set email alerts
|

Increase in resistance to anticancer drugs involves occludin in spheroid culture model of lung adenocarcinoma A549 cells

Abstract: Chemoresistance is a serious issue in the therapy of many cancers, but the molecular mechanism is little understood. The mRNA level of occludin (OCLN), a tight junctional protein, was increased in the cisplatin (CDDP), doxorubicin (DXR), 7-ethyl-10-hydroxy-camptothecin, or gemcitabine-resistant human lung adenocarcinoma A549 cells. Here, we investigated the regulatory mechanism and pathophysiological role of OCLN. OCLN was mainly localized at tight junctions in A549 and CDDP-resistant A549 (A549/CDDP) cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The in vitro inhibitory effects of the compounds were measured by MTT assay [ 59 , 60 ]. Briefly, cells were plated in 96-well plates at a density of 1 × 10 4 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro inhibitory effects of the compounds were measured by MTT assay [ 59 , 60 ]. Briefly, cells were plated in 96-well plates at a density of 1 × 10 4 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…Occludin contains a transmembrane domain with four membrane-spanning regions and other protein domains such as a C-terminus coiled-coil domain to interact with other proteins [ 200 , 203 ] . OCLN’s protein expression can influence the development of several cancer types, including ovarian cancer [ 200 ] , lung adenocarcinoma [ 203 , 205 ] , and breast cancer metastasis [ 206 ] . Zhang et al [ 200 ] (2018) reported that OCLN overexpression increased transepithelial resistance, which indicates stronger TJs, while downregulation of OCLN resulted in a decreased cell to cell adhesion phenotype (a common characteristic of tumors).…”
Section: Cancer Drug Resistance Related Genesmentioning
confidence: 99%
“…The overexpression of OCLN induces drug resistance by inhibiting the flux of doxorubicin, thus lowering drug concentration within the cell. OCLN may not be related to cancer drug resistance acquisition directly, but it limits the chemosensitivity of anticancer drugs to lung cancer cells [ 205 ] .…”
Section: Cancer Drug Resistance Related Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these cell culture models help answer some of the key questions, they may accompany multifactorial complexities. For example, the nonuniformity in the spheroid size contributes to the poor reproducibility of the cell response to cytotoxic drugs [9,10]. Also, large spheroids are devoid of any vasculature in the middle and hence the potential failure of drug delivery to the entire multicellular spheroid could be an important factor in reduced chemosensitivity rather than cellular resistance [11].…”
mentioning
confidence: 99%